Pengaruh Human Capital terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah Tahun 2010–2017 - Pradnya Paramitha; Harini Harini; Budi Wahyono (Department of Economics Education, Universitas Sebelas Maret, 2019)
Economic growth is a benchmark to see how the economic conditions in a region. In Central Java Province, economic growth is still a problem because of its position in the bottom two of the other provinces. The study aims to examine whether there is (1) the simultaneous impact between education, health, and employment on economic growth; (2) the impact of education on economic growth; (3) the impact of health on economic growth; (4) the impact of employment on economic growth. This study used quantitative methods with multiple regression analysis models. The subjects in this study were Central Java Province with a period of 2010–2017. The objects in this study were education, health, and employment. Data collection through the official website of the Badan Pusat Statistik (BPS). The data used was secondary data in the form of panel data. The results of the study are as follows: First, there is a positive and significant impact simultaneously between education, health, and employment on economic growth. Second, there is a positive and significant impact between education on economic growth. Third, there is a positive and significant impact between health on economic growth. Fourth, there is a positive and significant impact between employment on economic growth.